2016
DOI: 10.1111/bjh.14374
|View full text |Cite
|
Sign up to set email alerts
|

Is it possible to cure childhood acute myeloid leukaemia without significant cardiotoxicity?

Abstract: Since cardiotoxicity is a life threatening late effect, a reduction of cardiotoxicity in the treatment of acute myeloid leukaemia (AML) is essential. This review is a compilation of the current knowledge about cardiotoxicity after AML treatment and of how future directions in treatment may affect its incidence. A total of six studies concerning AML and cardiotoxicity were identified. The incidence of late subclinical cardiotoxicity varied between 1·3 and 15·3%, and late clinical cardiotoxicity varied between 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…Allogeneic stem cell transplantation is one of the approaches that is used in AML when other therapy options are exhausted 6 . Moreover, pediatric patients who recover from AML are prone to develop long‐term side effects such as growth delay, second cancers, cardiac toxicity, and cognitive problems 7‐10 . Thus, a novel treatment, effective enough to eliminate cancer cells with minimal influence on normal bodily functions, is needed, especially for pediatric AML patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allogeneic stem cell transplantation is one of the approaches that is used in AML when other therapy options are exhausted 6 . Moreover, pediatric patients who recover from AML are prone to develop long‐term side effects such as growth delay, second cancers, cardiac toxicity, and cognitive problems 7‐10 . Thus, a novel treatment, effective enough to eliminate cancer cells with minimal influence on normal bodily functions, is needed, especially for pediatric AML patients.…”
Section: Introductionmentioning
confidence: 99%
“…from AML are prone to develop long-term side effects such as growth delay, second cancers, cardiac toxicity, and cognitive problems. [7][8][9][10] Thus, a novel treatment, effective enough to eliminate cancer cells with minimal influence on normal bodily functions, is needed, especially for pediatric AML patients. Large-scale sequencing and transcriptomics studies of AML patients have identified several novel targets for drug development.…”
mentioning
confidence: 99%
“…Recent studies highlighted that midostaurin accompanied with standard chemotherapy significantly prolonged overall event-free survival for AML patients with a FMS-like tyrosine kinase 3 (FLT3) mutation [4]. While daunorubicin, idarubicin, cytarabine and doxorubicin remain the standard therapy for AML, the drug has been reported with a few cardiotoxic effects, a well-known risk factor for congestive heart failure [5]. AML is an incurable disease with relapse possibilities and conventional therapies have shown side-effects such as hepatotoxicity, myelosuppression, and tumor lysis syndrome [6].…”
Section: Introductionmentioning
confidence: 99%
“…Doxorubicin is used to treat numerous cancers for both adult and pediatric populations, such as breast cancer, Hodgkin's lymphoma in adults, and acute lymphoblastic leukemia, and acute myeloid leukemia in pediatrics. 6,7 Daunorubicin is usually utilized in the treatment of acute leukemias in both adults and pediatrics, whereas epirubicin is mostly used for breast cancer in adults and relapsed sarcoma in children. 8 Idarubicin use in adult and pediatric cancers is still minimal compared with the other anthracyclines.…”
Section: Clinical Background Of Anthracyclinesmentioning
confidence: 99%
“…There are currently four anthracyclines that are commonly used in clinical practice: doxorubicin, daunorubicin, epirubicin, and idarubicin, with doxorubicin being the most common. Doxorubicin is used to treat numerous cancers for both adult and pediatric populations, such as breast cancer, Hodgkin’s lymphoma in adults, and acute lymphoblastic leukemia, and acute myeloid leukemia in pediatrics 6,7 . Daunorubicin is usually utilized in the treatment of acute leukemias in both adults and pediatrics, whereas epirubicin is mostly used for breast cancer in adults and relapsed sarcoma in children 8 .…”
Section: Clinical Background Of Anthracyclinesmentioning
confidence: 99%